Analisis pertumbuhan ekonomi Indonesia dengan VECM: peran instrumen syariah dan makroekonomi - Istianah Latifatuzzahra; Nayli Kurnia Ilahi; Elsya Anggraini (Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the influence of Sharia Stocks, Sharia Mutual Funds, the Indonesian Composite Index (IHSG), and inflation on Indonesia’s Gross Domestic Product (GDP) in both the short and long run during the 2011-2024 period. The research is motivated by the dynamic development of Indonesia’s capital market and previous study indicating nonlinear relationships between capital market instruments and economic growth. Using the Vector Error Correction Model (VECM), the study conducts a series of procedures, including stationarity testing, optimal lag selection, Johansen cointegration testing, VECM estimation, Granger causality testing, impulse response function (IRF), variance decomposition (VD), and forecasting. The results reveal three cointegrating vectors, confirming stable long-run relationships among the variables. The IRF results show that shocks in sharia stocks and the IHSG significantly affect GDP, whereas the impact of inflation is relatively small. The VD analysis further indicates that sharia stocks contribute the most to GDP fluctuations in the medium term. These findings highlight the critical role of both sharia and conventional capital markets in supporting Indonesia’s economic growth and underline the strong interdependence between financial market dynamics and the real economy.